Debris Flow Mapping at Sungai Mandi, Santubong, Sarawak - Zarime N.A.; Bachat J.; Solemon B.; Omar R.C.; Wahab W.A.; Taher T.M.; Jaapar A.R.; Roslan R.; Aripin F.S.; Isa A.A.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Debris flows have always been a major issue in hilly environments. This paper concerns about the debris flow event along Sungai Mandi, Santubong which caused damage to property, buildings and roads at the river mouth. The main objective of this study is to determine the root cause of the debris flow event and to provide a better understanding on the debris flow mechanism and structures at risk at Santubong, Sarawak. A comprehensive assessment on geological, geomorphological, topographical, hydrological conditions and rainfall assessment concerns was conducted, where debris flow hazard factors were identified and assessed. Such hazard factors included the presence of boulder deposits, colluvium, relic landslide, riverbank erosion, boulders accumulated or trapped along river valley that created the temporary natural dams, which can contribute to further debris flow event in future. In addition, kinematic failure analysis was conducted to determine the rockfall failure potential as well as aerial photo interpretation on lineament and relic landslide. The interpretations and assessment would allow the results to be used to produce the debris flow risk map (buffer and danger zones) and debris flow anatomy zones. Furthermore, these assessments are critical for making judgements when evaluating the debris flow mechanism that could affect the tourism activities at Santubong Peninsula. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.